2000
DOI: 10.1152/ajpheart.2000.279.3.h1283
|View full text |Cite
|
Sign up to set email alerts
|

Selegiline improves cardiac sympathetic terminal function and β-adrenergic responsiveness in heart failure

Abstract: Selegiline is a centrally acting sympatholytic agent with neuroprotective properties. It also has been shown to promote sympathetic reinnervation after sympathectomy. These actions of selegiline may be beneficial in heart failure that is characterized by increased sympathetic nervous activity and functional sympathetic denervation. Twenty-seven rabbits with rapid cardiac pacing (360 beats/min, 8 wk) and twenty-three rabbits without pacing were randomly assigned to receive selegiline (1 mg/day, 8 wk) or placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Findings indicate that decrease of cardiac sympathetic transmitters in heart failure is associated with NE-mediated reduction of NGF and TrKA. nerve growth factor; norepinephrine; sympathetic efferent nerve fibers WE HAVE SHOWN PREVIOUSLY (14,16,31) that the cardiac sympathetic efferent postganglionic nerve terminal function is abnormal in chronic heart failure (CHF) as…”
mentioning
confidence: 99%
“…Findings indicate that decrease of cardiac sympathetic transmitters in heart failure is associated with NE-mediated reduction of NGF and TrKA. nerve growth factor; norepinephrine; sympathetic efferent nerve fibers WE HAVE SHOWN PREVIOUSLY (14,16,31) that the cardiac sympathetic efferent postganglionic nerve terminal function is abnormal in chronic heart failure (CHF) as…”
mentioning
confidence: 99%
“…In mature or stable neurons, GAP43 usually exists in the form of no expression or low expression, but its expression increases throughout the development and regeneration of the nervous system, so the expression of GAP43 also symbolizes the growth of nerves [ 48 ]. A number of experiments [ 49 , 50 ] have verified that the expression of GAP43 factor and NGF increase at the same time, indicating the rapid growth of related nerves, especially after myocardial infarction. Zhou et al [ 25 ] found that the level of NGF and GAP43 messenger ribonucleic acid in the LSG increased significantly after MI, thereby increasing the density of cardiac nerves.…”
Section: Discussionmentioning
confidence: 99%
“…14 In this model, marked downregulation of NE uptake function and uptake-1 density already occur after 2 weeks of pacing. 14 Treatment with the monoamine oxidase type B inhibitor selegiline 15 or with angiotensin-converting enzyme inhibitors 16 resulted in a reversion of these alterations and in a concomitant attenuation of the hemodynamic alterations caused by rapid pacing. It is currently unclear, however, whether downregulation and decreased activity of uptake-1 in heart failure are coincidental or causally related.…”
mentioning
confidence: 99%